Conclusions reported in European Orthodontic Congress poster abstracts: are they based on clinical or statistical significance? - Yip, Dawn Anne Xinying; Cobourne, Martyn T; Pandis, Nikolaos; Seehra, Jadbinder (European journal of orthodontics, 2025)
Abstract Background P-values convey statistical significance while effect estimates and confidence intervals (CIs) place emphasis on the clinical significance. The aim of this study was to determine the frequency of reporting clinical or statistical significance in European Orthodontic Society (EOS) Congress scientific poster abstracts and to ascertain whether the conclusions drawn are based on either clinical or statistical significance. Materials and methods Abstracts published between 2014 and 2024 were included. Pre-piloting and calibration were undertaken prior to data collection. Abstract characteristics were extracted independently by two reviewers. Descriptive statistics and frequency distributions were calculated. Results A total of 3654 abstracts were analysed. The highest number of abstracts were presented in 2018 (13.0%). Epidemiological studies (cross-sectional, case-control, cohort, survey) (54.7%) were frequently presented, followed by laboratorial studies (17.4%) and systematic reviews (7.7%). No inferential statistics were commonly reported (58.5%). Within the abstracts reporting statistical significance (41.1%), typically only P-values were reported (32.5%), followed by the term ‘statistically significant’ stated only (3.7%), P-values in conjunction with estimates and 95% CIs (1.7%), P-values and 95% CIs (1.4%), 95% CIs (0.8%), estimates and 95% CIs (0.6%), and P-values and estimates (0.4%). When interpreting the reported results in the conclusion section, these were typically based on P-values (31.2%) or the term ‘statistically significant’ stated only, without consideration of outcomes between groups (14.7%). 95% CIs (0.7%), P-values and 95% CIs (1.3%), P-values in conjunction with estimates and 95% CIs (1.6%) and estimates and 95% CIs (0.5%) were infrequently considered. Across the study timeframe (per year), the results and author conclusions tended to be based on P-values primarily. Limitations Only one society congress was assessed which may impact the generalizability of the results. Conclusions Clinical significance is often under-reported in abstracts presented at EOS. Where applicable the reporting of clinical significance (effect size with CIs) and their interpretation in poster abstracts should be stipulated as this allows clinicians to gauge both the size and range of the observed differences between groups and the relevance to their clinical practice.